2016
DOI: 10.1002/2015jd023981
|View full text |Cite
|
Sign up to set email alerts
|

Origins of tropospheric ozone interannual variation over Réunion: A model investigation

Abstract: International audienceObservations from long-term ozone sonde measurements show robust variations and trends in the evolution of ozone in the middle and upper troposphere over Réunion Island (21.1°S, 55.5°E) in June–August. Here we examine possible causes of the observed ozone variation at Réunion Island using hindcast simulations by the stratosphere-troposphere Global Modeling Initiative chemical transport model for 1992–2014, driven by assimilated Modern-Era Retrospective Analysis for Research and Applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 83 publications
0
24
0
Order By: Relevance
“…Recent developments in global chemistry models towards representing tropospheric and stratospheric chemistry as a single entity (Morgenstern et al, 2017 and references therein) will allow the uncertainty in the stratospheric impact on the troposphere to be evaluated more comprehensively (e.g., CCMI). Extensive evaluation of these models against more meaningful diagnostics that provide information on transport between the stratosphere and troposphere (e.g., Neu et al, 2014;Orbe et al, 2015;Liu et al, 2016) will help build confidence in the model simulated stratospheric contribution to tropospheric ozone.…”
Section: Representation Of the Stratospherementioning
confidence: 99%
“…Recent developments in global chemistry models towards representing tropospheric and stratospheric chemistry as a single entity (Morgenstern et al, 2017 and references therein) will allow the uncertainty in the stratospheric impact on the troposphere to be evaluated more comprehensively (e.g., CCMI). Extensive evaluation of these models against more meaningful diagnostics that provide information on transport between the stratosphere and troposphere (e.g., Neu et al, 2014;Orbe et al, 2015;Liu et al, 2016) will help build confidence in the model simulated stratospheric contribution to tropospheric ozone.…”
Section: Representation Of the Stratospherementioning
confidence: 99%
“…Models show that stratospheric ozone depletion has propagated to the upper troposphere . However, work based on the Southern Hemisphere Additional OZonesonde (SHADOZ) network suggests stratospheric mixing may be increasing upper-tropospheric ozone near southern Africa (Liu et al, 2015;Thompson et al, 2014). Uncertainties in the various processes which produce tropospheric ozone limit predictions of future ozoneinduced radiative forcing.…”
Section: Introductionmentioning
confidence: 99%
“…While the frequency, seasonality, and impacts of STT events have been well described in the tropics and Northern Hemisphere (NH), observational estimates from the SH extratropics are noticeably absent in the literature. The role of STT in the SH remains highly uncertain due to the more limited data availability compared to the NH and the temporal sparsity of these datasets (Mze et al, 2010;Thompson et al, 2014;Liu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…As inferred from models, both of the chemical production and loss budget terms are generally about an order of magnitude larger than the STE (Stevenson et al, ). However, STE contributes significantly to the interannual variability of tropospheric ozone (e.g., Liu et al, ; Liu et al, ; Sekiya & Sudo, ; Zeng & Pyle, ). Neu et al () found that about 16% of the Northern Hemisphere (NH) midlatitude zonal mean ozone variability is forced by STE.…”
Section: Introductionmentioning
confidence: 99%